COMPRESSIVE STRENGTH OF COMPOUNDS WITH WASTES OF ORGANIC ORIGIN - Bojórquez, Inocente; Pérez, María Milagrosa; Flores, Fernando; Bojórquez, Gonzalo (Revista Ingeniería de Construcción, 2003)
The aim of this work was to demonstrate the compressive strength of a compound of organic origin which contains ligneous fibres from mahogany (Swietenia machrophylla). These ligneous fibres were mixed, in the first sample, with Portland cement, and in the other sample with Portland cement and pulverized limestone. Both meant to be used as constructive elements. The work consisted, based on the former strength parameter, of the analysis of two ten-sample groups; one of them dried, the other one humid, both of them were made of the two above mentioned different kinds of mixtures. The results are shown in two graphs of each of the groups; humid or dried. It could then be seen that the humid compounds made out of fibres and cement only, were the ones that reached the highest values. These values then demonstrate the possibility of obtaining an alternative/alternating material of organic origin capable of being used in housing construction. The acquiring of the raw material/for which aids in the handling of the forest/ wouldn’t mess with the forest.